Reserving a Place for Nature on Spaceship Earth: Rethinking the Role of Conservation Easements - Kammer, Sean M.; Christopherson, Sarah E. (Columbia Journal of Environmental Law, 2019)
It has been over half a century since Kenneth Boulding introduced the metaphor of the Earth as a “spaceship.” In his compelling analogy he argued that, due to increasing human demands, the Earth was becoming more like a spaceship carrying limited supplies (and limited capacity to receive pollution) than an open prairie spreading endlessly to the horizon. In what he called the “cowboy economy,” “consumption is regarded as a good thing and production likewise,” with the economy’s success being measured solely “by the amount of the throughput from the ‘factors of production.’” Boulding pointed out that a portion of this throughput is necessarily “extracted from the reservoirs of raw materials and noneconomic objects” and that another part consists of “output into the reservoirs of pollution.” In the “spaceman economy,” in contrast, “throughput is by no means a desideratum, and is indeed to be regarded as something to be minimized rather than maximized.” There the measure of success is not production and consumption, but rather “the nature, extent, quality, and complexity of the total capital stock,” a term of art referring to the people and their satisfaction-yielding assets, whether natural or artificial. Boulding intended his “spaceship” analogy to emphasize the limitedness of the Earth’s natural resources, a fact mainstream economists had long ignored, despite its common-sense obviousness to those untrained in the economic sciences. While his ideas gained traction within a certain segment of the economics academy, even spawning a new field called “ecological economics,” they remain largely outside of mainstream economic, political, and legal discourse. That is unfortunate, as experiences of the last fifty years have only confirmed Boulding’s central thesis. The Earth is indeed finite, and the human economy is pushing up against, if not already exceeding, its boundaries. The scale of our economic activities now threatens to alter some of the Earth’s most fundamental processes, including those upon which our economy—and hence our well-being—relies. As awareness of the need for conservation has increased, so too has the use of conservation easements—an instrument whereby landowners sell or donate certain of their development rights to another party in exchange for certain tax benefits—as one tool among many for meeting that need. Conservation easements now protect about forty million acres within the United States. Their use of private property mechanisms to serve public purposes is a key reason for their popularity among conservation organizations and landowners alike. Still, they are not without their issues. What legal scholar Fred Cheever noted in 1996 remains largely true today: “some dark omens cloud the future of the movement and, absent some changes in the legal structures that support it, time may erode the happy congruity between public and private at the cost of the environment and the public good.” These legal and policy issues include the lack of coordinated landscape-scale planning, the lack of accountability for private owners of easements in enforcing the terms of their holdings, abuses of tax codes, and their inflexibility in responding to changing social or economic conditions. These issues have prompted calls for reforming the legal regime governing conservation easements—calls some states have answered in their own ways. Much more remains to be done. This Article proceeds in three parts. Part II describes the field of ecological economics, including its central critiques of mainstream economic models, it explains the urgency of the conservation effort, and it outlines the role of conservation easements in the wider environmental portfolio. Part III describes some of the major problems arising from the use of conservation easements, including some that could arguably render them not just inefficient, but actually counterproductive to their conservationist purpose. Part IV assesses several proposals aimed at addressing these concerns, including some measures states have already adopted. It concludes with a call for states and the federal government to radically reform their methods for valuing conservation easements for tax purposes, namely by using insights from ecological economics to determine each easement’s actual contribution to human welfare in the present and future. Only then will private parties supply conservation services and goods at the level society truly demands and needs.